“TO USE BUFFALO STRENGTH”: ANIMAL METAPHORS IN AFRICAN IDIOMS BASED ON EXAMPLES FROM THE FON LANGUAGE IN BENIN - Lanmadousselo, Sewanou Martial Jupiter (Proverbium - Yearbook, 2023)
An animal metaphor is spoken of when animal characteristics, among other things, are transferred to humans and their behaviour. In order to illustrate the peculiarity and character of the Fon language, 37 Fon (Benin) expressions are selected as examples in this study. The focus is entirely on animal metaphors. The selected Fon idioms are, on the one hand, transcribed and translated into German, and on the other hand, contextually annotated in order to highlight their semantic meanings. The latter is illustrated by example.